New species of Helpis Simon, 1901 from Australia (Araneae: Salticidae), with a new definition of the genus - Żabka, Marek; Patoleta, Barbara M. (Zootaxa, 2014)
Five new species of Helpis Simon, 1901 from Queensland and New South Wales are diagnosed, described and illustrated: H. foelixi sp. nov. (♂); H. merriwa sp. nov. (♀); H. staregai sp. nov. (♀); H. wanlessi sp. nov. (♀) and H. wisharti sp. nov. (♀). The male of H. kenilworthi Żabka, 2002 is described for the first time, Helpis gracilis Gardzińska, 1996 is illustrated to show intraspecific variation and Astia colemani Wanless, 1988 is redescribed and transferred to the genus Helpis. Remarks on relationships of described species are provided and maps with distributional records are given.